"Old" carbon entering the South China Sea from the carbonate-rich Pearl River Basin: Coupled action of carbonate weathering and aquatic photosynthesis. (March 2017) - Liu, Zaihua; Zhao, Min; Sun, Hailong; Yang, Rui; Chen, Bo; Yang, Mingxing; Zeng, Qingrui; Zeng, Haitao
Abstract: Generally, negative Δ 14 C values of riverine particulate organic carbon (POC) are interpreted as old carbon derived from the erosion of deep soils and sedimentary rocks. Here we present natural 14 C and 13 C data from the carbonate-rich Pearl River Basin that discharges into the South China Sea. We found that the Δ 14 C values of POC and DIC (dissolved inorganic carbon) transported by the carbonate-rich river are all negative. This, however, does not mean the POC is necessarily old but indicates control of carbonate weathering (producing "old" DIC with negative Δ 14 C values) coupled with contemporary aquatic photosynthesis (producingnew autochthonous POC but with negative Δ 14 C values) through the "dead carbon" effect of carbonate rocks, which was further evidenced by particular seasonal change in Δ 14 C values of DIC and POC (both higher in the rainy season and lower in dry season), spatial variation (both getting higher downstream), and negative correlation between δ 13 C and "age" of POC. This finding indicates that previous studies suggesting that riverine POC depleted in 14 C is old may be problematic in carbonate-dominated river basins. The finding that river basins rich in carbonates can release "old" POC may have important implications for the interpretation of organic carbon age in rivers and coastal oceans affected by the runoff from this basin type. It also indicates that it is necessary to examine the concentrations of both DIC and autochthonous organic carbon in rivers to correctly assess the carbon sink produced by rock weathering. Highlights: Negative Δ 14 C value of river POC does not mean the POC is necessarily old. It may indicate carbonate weathering coupled with present aquatic photosynthesis. This has implications for the interpretation of organic carbon age in surface waters.